Waktu Realistis Pengerjaan Proyek Rumah Tinggal Bertingkat Type 72 Dengan Metode Program Evaluation and Review Technique (PERT) di PT. XYZ Medan - Eddy Eddy; Abdul Gani Syahputra (Jurnal Optimalisasi, 2020)
The complexity of managing a project requires good and accurate planning. This is done to overcome the obstacles that arise in the implementation of project work. One of them is the obstacle of late project completion time. Program Evaluation and Review Technique (PERT) is a network model that is able to map the time of completion of activities. PERT is very useful for managing a project because it provides information relating to the completion of a project. The use of PERT method in this study provides the results of the completion time of type 72-storey residential building project based on a critical trajectory of 114 days. Through a statistical approach and assuming the completion of a normally distributed project the realistic time span of completion of the project is between 114 days to 124 days. While the probability of completion of the project during the time frame is between 50% to 99.9%.